Reversible physical crosslinking strategy with optimal temperature for 3D bioprinting of human chondrocyte-laden gelatin methacryloyl bioink. (November 2018) - Gu, Yawei; Zhang, Lei; Du, Xiaoyu; Fan, Ziwen; Wang, Long; Sun, Weiyan; Cheng, Yu; Zhu, Yufang; Chen, Chang
Gelatin methacryloyl is a promising material in tissue engineering and has been widely studied in three-dimensional bioprinting. Although gelatin methacryloyl possesses excellent biocompatibility and tunable mechanical properties, its poor printability/processability has hindered its further applications. In this study, we report a reversible physical crosslinking strategy for precise deposition of human chondrocyte-laden gelatin methacryloyl bioink at low concentration without any sacrificial material by using extrusive three-dimensional bioprinting. The precise printing temperature was determined by the rheological properties of gelatin methacryloyl with temperature. Ten percent (w/v) gelatin methacryloyl was chosen as the printing formula due to highest biocompatibility in three-dimensional cell cultures in gelatin methacryloyl hydrogel disks. Primary human chondrocyte-laden 10% (w/v) gelatin methacryloyl was successfully printed without any construct deformation or collapse and was permanently crosslinked by ultraviolet light. The printed gelatin methacryloyl hydrogel constructs remained stable in long-term culture. Chondrocyte viability and proliferation that were printed under this optimal temperature were better than that of chondrocytes printed under lower temperatures and were similar to that of chondrocytes in the non-printed gelatin methacryloyl hydrogels. The results indicate that with this strategy, 10% (w/v) gelatin methacryloyl bioink presented excellent printability and printing resolution with high cell viability, which appears to be suitable for printing primary human chondrocytes in cartilage biofabrication and can be extensively applied in tissue engineering of other organs or in other biomedical fields.